2000
DOI: 10.1603/0022-0493-93.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Western Flower Thrips (Thysanoptera: Thripidae) in Nectarine Orchards in British Columbia

Abstract: Development of a control strategy for thrips attacking nectarine trees depends on an understanding of their phenology, distribution, and life history as related to characteristics of nectarine orchards. To this end, we compared the overwintering behavior, distribution, and abundance of western flower thrips, Frankliniella occidentalis (Pergande), among 11 nectarine orchards located in the dry central interior of British Columbia, Canada, during 1993 and 1994. Western flower thrips emerged from areas not previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 15 publications
(15 reference statements)
2
27
0
3
Order By: Relevance
“…It is possible that some eggs were laid even before bud swelling, possibly over the winter, although this is still to be determined. Western ßower thrips overwinter on nectarine trees (Pearsall and Myers 1999), and as the tree bark is warmed on sunny days during the winter, it is possible that the thrips may become active and oviposit in the dormant buds. Although eggs were laid continuously throughout development of the bud, most were laid during early bud stages.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some eggs were laid even before bud swelling, possibly over the winter, although this is still to be determined. Western ßower thrips overwinter on nectarine trees (Pearsall and Myers 1999), and as the tree bark is warmed on sunny days during the winter, it is possible that the thrips may become active and oviposit in the dormant buds. Although eggs were laid continuously throughout development of the bud, most were laid during early bud stages.…”
Section: Discussionmentioning
confidence: 99%
“…Included were 29 emasculated, previously unvisited flowers (see Murza and Davis 2005) that we watched for the first visitor (Site 1: 7 flowers for 327 min. in 2000, 4/150 -2001Site 2: 7/213 -2000Site 2: 7/213 - , 11/509 -2001 with the objective to quantify the potential pollination activity of individual insect species (Murza and Davis 2005). We also observed visitors to 53 other intact, non-experimental flowers of unknown visitation history (Site 1: 25/172 -2000(Site 1: 25/172 - , 19/399 -2001Site 2: 9/101 -2001).…”
Section: Observations and Capture Of Flower Visitorsmentioning
confidence: 99%
“…Although the larvae could not be identified beyond genus, a total of four winged adults of T. fallaciosus captured by leaves could be the same species. A lack of movement of wingless T. fallaciosus larvae outside nectarine flowers, and their falling from flowers to the ground to pupate (Pearsall and Myers 2000), suggest that the nonwinged larva may have fallen, rather than wandered from a flower, onto a trap leaf below. Based on the identified flower visitors and prey items, the evidence strongly suggests that D. anglica rarely traps and consumes on its leaves, those visitors to its flowers.…”
Section: Comparison Of Prey Taxa On Leaves With Visitors To Flowersmentioning
confidence: 99%
“…Pickett et al (1988) revealed that migration plays an important role in the population dynamic and changing age structure of thrips. Pearsall and Myers (2000) informed that exposure of orchards to a wind flow which carries dispersing thrips may play a role in thrip movement. Remark: Flw = Flower, Lvs = Leaves Sex ratio observation also indicated an equality between male and female toward all age structures i.e.…”
Section: Age Structure and Sex Ratio Of S Dorsalis In Mango Orchard mentioning
confidence: 99%